2013
DOI: 10.1186/1471-2369-14-62
|View full text |Cite
|
Sign up to set email alerts
|

Renal dysfunction in STEMI-patients undergoing primary angioplasty: higher prevalence but equal prognostic impact in female patients; an observational cohort study from the Belgian STEMI registry

Abstract: BackgroundMortality in female patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary angioplasty (pPCI) is higher than in men. We examined gender differences in the prevalence and prognostic performance of renal dysfunction at admission in this setting.MethodsA multicenter retrospective sub-analysis of the Belgian STEMI-registry identified 1,638 patients (20.6% women, 79.4% men) treated with pPCI in 8 tertiary care hospitals (January 2007-February 2011). The estimated glomerular fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Additionally, mortality due to MI was more prevalent among females, which was consistent with the results of the studies by Valente and De Luca (21,22). However, some studies have come to controversial results (23,24) mainly because of women's clinical and profile risk factors.…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, mortality due to MI was more prevalent among females, which was consistent with the results of the studies by Valente and De Luca (21,22). However, some studies have come to controversial results (23,24) mainly because of women's clinical and profile risk factors.…”
Section: Discussionsupporting
confidence: 81%
“…These data are supported by previous reports. Both Gevaert et al and Sederholm Lawesson et al showed that female gender was independently associated with renal dysfunction at admission in PCI‐treated patients. Furthermore, Sciagra et al showed that among 460 patients with acute myocardial infarction, there was a significant gender‐related difference with left ventricular ejection fraction decreasing more sharply in females than in males.…”
Section: Discussionmentioning
confidence: 98%
“…Our finding has some potential clinical implications. We speculate that early nephroprotective strategies for contrast‐induced renal injury, such as low volume of contrast, crystalloid infusions, radial approach to prevent bleeding and other complications, measures for optimal hemodynamics, and discontinuation of nephrotoxic drugs, might provide a significant long‐term benefit . The possibility of early identification of the patients who will probably develop DRF is clinically important.…”
Section: Discussionmentioning
confidence: 99%